Correspondence between Her Majesty's government and the Hudson's Bay Company [electronic resource]. - Hudson's Bay Company. ([London? : s.n.], 1869)
Correspondence between the Colonial Office and the Hudson's Bay Company. At head title: Hudson's Bay Company. Electronic reproduction. Mode of access: Internet. 44